Wielkopolskie Słowniki Regionalne okolic Gniezna w kontekście potrzeb badawczych tej części regionu - Kobus, Justyna (Slavia Occidentalis, 2023)
The article presents the state of dialectological documentation for the area of today’s Gniezno County. The author statistically summarized Adam Tomaszewski’s pre-war materials, providing the number of index cards, and listed the research points and hours of recordings for the Atlas of the language and folk culture of Wielkopolska. Then the author cited statistics for contemporary materials, interpreted as field explorations after 2000, deposited in the audio library of the Dialectology Laboratory of Adam Mickiewicz University in Poznań. Explorations related to the development of dictionaries as part of the Wielkopolska Regional Dictionary series have been distinguished, which extend the source database many times in relation to its existing content. This situation proves the need to conduct field research, e.g. using the educational project method.